1998
DOI: 10.1016/s0005-2736(97)00222-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronopotentiometric studies of electroporation of bilayer lipid membranes

Abstract: The constant-intensity current chronopotentiometric measurements of egg yolk phosphatidylcholine bilayer membranes (BLM) are presented. It is demonstrated that a constant-intensity current flowing through the bilayer membranes generates the pores in their structures. For the current intensity from 0.1 to 2.0 nA, the generated pores open and close cyclically. The frequency of oscillations depends on the current intensity: the higher current intensity, the higher frequency of pore oscillations. It is suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…46 The measuring system 47 was comprised of four Ag-AgCl electrodes (2 current and 2 reference electrodes) and consisted of two modules allowing the measurement of the lipid bilayer capacitance and the voltage across the bilayer, and a potentiostat-galvanostat for the current control. The specific membrane (bilayer) capacitance (c BLM ) normalized to the surface area of the bilayer was measured with capacitance to period conversion.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…46 The measuring system 47 was comprised of four Ag-AgCl electrodes (2 current and 2 reference electrodes) and consisted of two modules allowing the measurement of the lipid bilayer capacitance and the voltage across the bilayer, and a potentiostat-galvanostat for the current control. The specific membrane (bilayer) capacitance (c BLM ) normalized to the surface area of the bilayer was measured with capacitance to period conversion.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…This effect is a sign of an electropore formation. Estimation of the electropore diameter indicates that usually a single nanopore is formed [21]. Short breaks in current supply do not let the electropore reseal [18].…”
Section: Resultsmentioning
confidence: 99%
“…Electropore conductance G p at any selected point (Fig. 4) was calculated by the method described previously [21] as:…”
Section: Calculation Of Electropore Conductance and Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that during these kinds of measurements, the lipid bilayer is more stable due to less voltage stress [27], [30]; therefore, small changes in the membrane structure can also be observed. Scalas et al [31], for example, reported on the time course of voltage fluctuations that followed an increase of the membrane conductance due to the opening and closing of hydrophilic pores [28], [31], [40].…”
mentioning
confidence: 99%